(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Annotation: The article discusses the life and work of Zahiriddin Mukhammad Bobur. Since the Timurid Empire was disintegrated after the death of Amir Timur, Bobur, a descendant of the Timurids, wanted to restore it. However, as the result of many failures in the battles, he created a new Empire of Baburids in India. Along with being a king, Bobur also worked as a poet. We have inherited many of his works dedicated to his country.